PENGARUH PRAKTIK KERJA INDUSTRI DAN HASIL BELAJAR TERHADAP KESIAPAN KERJA SISWA KELAS XII DI SMK SWASTA PALEMBANG - Agustina, Tri; Arafat, Yasir; Mulyadi, Mulyadi (STKIP Pesisir Selatan, 2026)
This study aims to determine and analyze the efluence of industrial work practice and learning outcomes on the work readiness of Grade XII students at Private Vocational School Palembang, both partially and simultaneously. The population in this study consisted of Grade XII industrial students at PGRI 2 Vocational School in Palembang and YP Gajah Mada Vocational School in Palembang, with a sample size of 108 students. The data collection techniques used in this study were: 1) questionnaires and 2) documentation. The data analysis technique used parametric statistics with the SPSS program. The results of this study concluded that: 1) There is a positive influence of industrial work practices on the work readiness of grade XII students at private vocational schools in Palembang. 2) There is no positive influence of learning outcomes on the work readiness of grade XII students at private vocational schools in Palembang. 3) There is a positive influence of industrial work practices and learning outcomes together (simultaneously) on the work readiness of grade XII students at private vocational schools in Palembang.